The Needs of Assistive Technology on Students’ EFL Writing - Dwi Sloria Suharti; Eka Ugi Sutikno (Globish: An English-Indonesian Journal for English, Education, and Culture, 2019)
Nowadays generally, technology encompasses all aspects of modern life and particularly, the writing by using English language. The challenges of learning English writing in Indonesia are plenty as English is perceived as a Foreign Language. This paper aims to reveal tertiary level students’ perception and attitude towards their technology aptitude: usage models, noticed benefits of and challenges to employ technology in learning English as Foreign Language (EFL) writing. This is a qualitative research, a case study, and used a self-structured questionnaire and interview to collect the data. Two participant lecturer observers and one hundred and sixty-seven students in a private college in Tangerang were purposively selected thirty students for questionnaire and interview. The data were carried out to reveal the lecturers and students’ perspective of assistive technology in EFL writing. The results revealed that assistive technology such as Webbing/Blogs, Computer software, Social Mediaapps, YouTubechannel, smart phone and tablet apps are found to be used by EFL learners to learn EFL Writing. Yet, most of the students had constraint at bad Internet connection. The outcome of this study offers thinkable instructional suggestions for students’ EFL Writing and creates base for further studies in this area.Keywords: Students’ EFL Writing, Learning EFL Writing, Assistive Technology